High‐entropy, phase‐constrained, lanthanide sesquioxide. Issue 1 (25th July 2019) - Tseng, Kuo‐Pin; Yang, Qun; McCormack, Scott J.; Kriven, Waltraud M.
Abstract: Oxides can experience structural transformations resulting from variations in cation oxidation states or coordination geometry upon thermal treatment. Whether such structural distortions can affect the stability of high‐entropy oxides has not been studied. In this research, a new, high‐entropy, lanthanide sesquioxide, Gd0.4 Tb0.4 Dy0.4 Ho0.4 Er0.4 O3 solid solution having a single phase, cubic‐bixbyite structure was synthesized, with no phase transformation from room temperature to 1650°C. The phase stability was examined via both in situ and ex situ, high‐temperature, synchrotron, X‐ray powder diffraction. This high‐entropy oxide could inhibit the phase transformations occurring in constituent monocation sesquioxides, Tb2 O3 and Gd2 O3, via random arrangement of multications.